Aerobic oxygenation of α-methylene ketones under visible-light catalysed by a CeNi3 complex with a macrocyclic tris(salen)-ligand. Issue 85 (7th October 2021) - Nagae, Haruki; Sakamoto, Kazutaka; Fujiwara, Sakiko; Schindler, Tobias; Kon, Yoshihiro; Sato, Kazuhiko; Okuda, Jun; Mashima, Kazushi
Abstract : A hetero-tetranuclear complex 1CeNi catalysed the aerobic oxygenation of a methylene group adjacent to a carbonyl group under visible-light radiation. Abstract : A hetero-tetranuclear CeNi3 complex with a macrocyclic ligand catalysed the aerobic oxygenation of a methylene group adjacent to a carbonyl group under visible-light radiation to produce the corresponding α-diketones. The visible-light induced homolysis of the Ce–O bond of a bis(enolate) intermediate is proposed prior to aerobic oxygenation.